Modernity in Mendoza (1890-1930): Cacheuta settlement as mountain testimony - Bianchi, Pablo Federico (Universidad ORT Uruguay, 2019)
This investigation focuses on the detection of a vacancy of an integral approaching of the cultural goods on the middle section of the Mendoza River, in the central portion of the Argentinian Andes. Nowadays it has been advanced only in a limited look in the study of historical goods that consolidated the territory, which impedes enormously the possibility of reincorporation of such goods as tourist and economic resource for the region.For the comprehension of the problem it has been proposed an approach to physical space of particular characteristics – sharp slopes, steep morphology of the soil surfaces, stocky vegetation– in a historical time that reveals the transition between the end of 19th century and the beginning of the 20th century, period known as the “modernity”. Starting from the methodology of case study we intended to reveal the coexistence of intentions and investments of public and private management. Particularly, in the area known as “Cacheuta valley”, where some of the effects of this modernity show the introduction of new technologies in productive processes, new ways of social interaction and established the foundations for the permanent historical settlement of this area. The railroad and the road plot constitute the guiding thread that leaded these pioneering interventions.